Public administration in the conditions of the development of digital economy and society - Matvejciuk, Liudmyla (Management and Entrepreneurship: Trends of Development, 2019)
The purpose of this paper is to study public administration in the context of the development of the digital economy and society. The basis of the methodology of the study is a systematic approach, using general scientific and special methods of scientific research. The categorical-conceptual apparatus of public administration is investigated, the author's interpretation of the definition is formed; digitalization is highlighted as one of the influential factors of the effectiveness of public administration; The evolutionary stages of the development of public administration are proposed: state administration → public administration → digital public administration, and digital public administration is considered as an innovative model of interaction between public authorities and digital society participants, built on the use of ICT and electronic communication channels. Electronic governance as an innovative form of public administration using ICT is highlighted; the materials of the UN research on the technological maturity of the countries in the field of e-government according to the index of development of the e-government have been analyzed, Ukraine's significant lagging rating has been identified, the research on the best practices of e-government leaders has been substantiated, including post-Soviet countries for decision-making in the field of public administration, and the formation of a state policy on the development of a digital government. The applied aspects of the development of digital Ukraine, which have been implemented in recent years, have been described, those include: strategic and normative documents, and state digital platforms. The next stage of digitalization of public administration is highlighted - the association of state information resources, the provision of integrated electronic services; the necessity of development of digital public administration is substantiated. The scientific significance of the paper is to study the process of development of public administration in the conditions of the digital economy and society. As conclusion, the necessity of the development of digital public administration as the basic precondition for the development and integration of the domestic digital economy into the global digital market has been substantiated. In practice, digitalisation of public administration will improve the quality of service for citizens and business and increase the openness, transparency and efficiency of public bodies.JEL Classification: H11